(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the level and current state of the study of ancient Chinese literature in Uzbekistan, as well as the formation of Sinology in Uzbekistan, the contributions of prominent scholars and translators, the theoretical analysis of the translation of ancient Chinese literary works into the Uzbek language is conducted.